Financial contagion of German industrial enterprises during the 2021–2023 global energy crisis - A. M. Terekhov; A. O. Ovcharov (Управление)
The relevance of the study is justified by the importance of capturing and assessing the financial contagion transmission in crisis for the purposes of identifying risks in the financial market, as well as for the industrial sector management at the micro and macro levels.   The article applies such an assessment to the largest industrial enterprises in Germany.   The object of study choice is due to the fact that Germany, on the one hand, has a highly developed industrial sector and, on the other hand, was the most severely affected by the global energy crisis caused by political disagreements at the international level.   The natural gas market has been chosen as a transmitter of contagion and German industrial companies as a receiver. A brief theoretical review considers the peculiarities of the functioning of the industrial sector of the German economy during the global energy crisis. The dependence of industrial production on natural gas imports has been revealed. The practical section captures financial contagion using the following tests: Forbes-Rigobon, distributional coasymmetry, distributional cocurtosis, and covolatility. A ranking of the industries contagion in Germany has been constructed. It has been found that most of the investigated companies are exposed to contagion from the gas market to a greater or lesser extent. Only three companies showed absolute resistance to contagion: Enbw Energie Baden Wuerttemberg AG, Stemmer Imaging AG, and OHB SE. The light industry, metals and mining were the most affected to the financial contagion, while the construction industry was the least affected.